PENGARUH PENDIDIKAN KESEHATAN RESUSITASI JANTUNG PARU TERHADAP KEMAMPUAN PENANGAN PRE HOSPITAL KORBAN HENTI JANTUNG PADA KARANGTARUNA DI KECAMATAN BALUNG : The Effect of Cardiopulmonary Resuscitation Health Education on the Ability to Handle Pre-Hospital Cardiac Arrest Victims at Karangtaruna in Balung District - Astri Shofiyah Sholikhah; Cipto Susilo; Mohammad Ali Hamid (Forind Press, 2024)
Cardiac arrest is an emergency case, occurs due to loss of blood and oxygen in the heart muscle. This research method uses a type of pre-experimental method with a pre-test post-test group design approach with a sample of 30 respondents from members of the youth organization. The results of the study showed that the ability to handle pre-hospital cardiac arrest victims before being given cardiopulmonary resuscitation health education was in the sufficient low value with a percentage of 7,26 prior, while the ability to handle pre-hospital cardiac arrest victims after was in the good category with a score 11,00. The results of the T-test were also obtained, showing a significant value of 0.000. So the p value is 0.000 <0.05. So it is expected to be able to improve the ability to handle members of the youth organization in providing basic life support for cardiac arrest victims appropriately in handling which is a pre-hospital action.